1996
DOI: 10.1128/jb.178.17.5222-5228.1996
|View full text |Cite
|
Sign up to set email alerts
|

An 18-base-pair sequence is sufficient for termination of rolling-circle replication of plasmid pT181

Abstract: pT181 and related plasmids of gram-positive bacteria replicate by a rolling-circle mechanism. The replication initiator protein of pT181, RepC, has origin-specific nicking-closing activities. Replication of the plasmid pT181 leading strand initiates by covalent extension of the RepC-generated nick, and the origin of replication contains signals for both initiation and termination of DNA replication. We have investigated the sequence requirements for the initiation and termination steps by using plasmids contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
(54 reference statements)
1
17
0
1
Order By: Relevance
“…3). As shown previously (Zhao and Khan, 1996), these miniplasmids were maintained at much higher copy numbers than the vector pSA7650 plasmid both at 32ЊC and 43ЊC, since replication supported by RepC provided in trans dominates in the presence of a fully functional pT181 origin over the pE194 replicon contained in pSA7650 (Fig. 3).…”
Section: In Vitro Initiation and Termination Activities Of The Variousupporting
confidence: 61%
See 4 more Smart Citations
“…3). As shown previously (Zhao and Khan, 1996), these miniplasmids were maintained at much higher copy numbers than the vector pSA7650 plasmid both at 32ЊC and 43ЊC, since replication supported by RepC provided in trans dominates in the presence of a fully functional pT181 origin over the pE194 replicon contained in pSA7650 (Fig. 3).…”
Section: In Vitro Initiation and Termination Activities Of The Variousupporting
confidence: 61%
“…The in vivo and in vitro replication termination activities of the various IRII mutants, along with their RepCdependent nicking activities are summarized in Table 1. Previous studies have shown that the IRII region of the pT181 origin by itself is sufficient for the termination of pT181 replication (Zhao and Khan, 1996). We tested the termination and initiation activities of IRII mutants to determine the role of its sequence and structure in these steps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations